Comparisons of Curative Effects of Chlorophyll from Sauropus androgynus (L) Merr Leaf Extract and Cu-Chlorophyllin on Sodium Nitrate-Induced Oxidative Stress in Rats - Suparmi Suparmi; Minidian Fasitasari; Martanto Martosupono; Jubhar Christian Mangimbulude (Journal of Toxicology)
Sodium nitrate (NaNO2) widely used as food additive for coloring and preserving meat has been reported to induce oxidative stress and cause histopathologic changes, nitrosative tissue damage, and lipid peroxidation in liver and kidney. Therefore, the present study compared the curative effect of chlorophyll from Sauropus androgynus (L) Merr and Cu-chlorophyllin as antioxidant in NaNO2-induced female Wistar rats based on haematological, serum biochemical, and histological evaluation. Thirty male Wistar rats were randomly assigned into six groups of five rats each. NaNO2 were given at a subacute dose of 50 mg/kg bw intraperitoneally for 10 days. Chlorophyll from S. androgynus and Cu-chlorophyllin from K-Liquid™ were given in the following 14 days at the two doses: 0,016 mg/mL and 0.008 mg/mL. NaNO2 exposure resulted in significant reductions (p<0.05) in values of packed cell volume (PCV), haemoglobin (Hb) concentration and red blood cell (RBC) count, transferrin, and ferritin and elevation in malondialdehyde (MDA) level and schistocytes percentage with insignificant reductions in serum albumin and transferrin levels. Histology of kidney and liver were changed insignificantly (p>0.05) to normal values. Chlorophyll from S. androgynus and Cu-chlorophyllin possess antioxidant potentials to protect against toxicities induced by sodium nitrate.